PERANAN PENDIDIKAN YANG DIPEROLEH DAN PENGALAMAN MENGAJAR TERHADAP KEMAMPUAN MENGAJAR GURU-GURU SEKOLAH DASAR DI UPT KECAMATAN KRETEK BANTUL - Wartomo . (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2016)
The problems were how far the role of education to the teaching capability, how farthe education experiences has play role to teaching capability and how far the educationand teaching experiences together have play role to the education capability for theelementary teachers on Technical Unit Location at Kretek Bantul Regency. While thereason of this research was to know the role of education and teaching experiences whetheras solitary or as together have a play role or not to the education capability of elementaryteachers on technical unit location at Kretek district Bantul regency. The method used inthis research was quota area random sampling, while the location for researches wereelementary schools located at Kretek district and time duration for research between July â€“Â August 2010. The amount of research personals subject were 30 persons. Data collectionused by observation technique and documentation as main technical method completedwith interview. While for data analysis, method used with single and double regressionmethods. The conclusion was : There were no significant difference on educated teacherson their capability (rxy = 0.162 < r = 0,374) there were no significant differenceteaching experience on teaching capability (rtable 5%x2xy = 0.124 < r = 0,374), There were nosignificant difference between education and experience as togetherness on teachingcapability Freg = 0,86 < F table 5% table 5%= 3,35) for the elementary teachers on local technical unitat Kretek district Bantul Regency.Key Words : teachers, roll of education, teaching experience, capability.Â